(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study experimentally investigates the effect of basin water depth on the performance of a single-slope solar still under the climatic conditions of Gandhinagar, Gujarat, India. Three basin water depths of 1 cm, 2 cm, and 3 cm were examined to evaluate their influence on basin water temperature, distillate productivity, and thermal efficiency. Experimental observations revealed that water depth significantly affects the evaporation and condensation processes within the solar still. The lowest water depth of 1 cm exhibited the highest basin water temperature, reaching approximately 69.5°C, due to its lower thermal mass and faster heating characteristics. Consequently, the maximum daily freshwater production of 3.40 L/m²·day was achieved at 1 cm depth, whereas the yields obtained at 2 cm and 3 cm depths were 2.95 L/m²·day and 2.51 L/m²·day, respectively. The corresponding thermal efficiencies were found to be 34.2%, 29.7%, and 25.3% for 1 cm, 2 cm, and 3 cm water depths, respectively. Compared with the 3 cm depth, the 1 cm depth enhanced freshwater productivity by approximately 35.5%. The results indicate that increasing water depth increases the thermal inertia of basin water, thereby reducing the water temperature rise and evaporation rate. Therefore, a shallow water depth of 1 cm is recommended as the optimum operating condition for maximizing freshwater production and improving the overall performance of solar still systems under the climatic conditions of Gandhinagar.